Preference for cesarean section in young nulligravid women in eight OECD countries and implications for reproductive health education - Kathrin H. Stoll; Yvonne L. Hauck; Soo Downe; Deborah Payne; Wendy A. Hall; International Childbirth Attitudes- Prior to Pregnancy (ICAPP) (BMC, 2017)
Abstract Background Efforts to reduce unnecessary Cesarean sections (CS) in high and middle income countries have focused on changing hospital cultures and policies, care provider attitudes and behaviors, and increasing women's knowledge about the benefits of vaginal birth. These strategies have been largely ineffective. Despite evidence that women have well-developed preferences for mode of delivery prior to conceiving their first child, few studies and no interventions have targeted the next generation of maternity care consumers. The objectives of the study were to identify how many women prefer Cesarean section in a hypothetical healthy pregnancy, why they prefer CS and whether women report knowledge gaps about pregnancy and childbirth that can inform educational interventions. Methods Data was collected via an online survey at colleges and universities in 8 OECD countries (Australia, Canada, Chile, England, Germany, Iceland, New Zealand, United States) in 2014/2015. Childless young men and women between 18 and 40 years of age who planned to have at least one child in the future were eligible to participate. The current analysis is focused on the attitudes of women (n = 3616); rates of CS preference across countries are compared, using a standardized cohort of women aged 18-25 years, who were born in the survey country and did not study health sciences (n = 1390). Results One in ten young women in our study preferred CS, ranging from 7.6% in Iceland to 18.4% in Australia. Fear of uncontrollable labor pain and fear of physical damage were primary reasons for preferring a CS. Both fear of childbirth and preferences for CS declined as the level of confidence in women's knowledge of pregnancy and birth increased. Conclusion Education sessions delivered online, through social media, and face-to-face using drama and stories told by peers (young women who have recently had babies) or celebrities could be designed to maximize young women's capacity to understand the physiology of labor and birth, and the range of methods available to support them in coping with labor pain and to minimize invasive procedures, therefore reducing fear of pain, bodily damage, and loss of control. The most efficacious designs and content for such education for young women and girls remains to be tested in future studies.